Family Burdens in patients with Schizophrenia - Sustrami, Dya; Yusuf, Ah; Fitryasari, Rizki; Suhardingsih, A.V. Sri (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Introduction: People with schizophrenia need the role of the family as a caregiver. Objectives: The aim of this study was to describe the burden of the family as a caregiver for schizophrenia patients in an outpatient polyclinic setting, Menur Mental Health Hospital Surabaya. Methods: Total participants were 160 family caregivers who carry out routine check-ups for families with schizophrenia. The data was obtained using the Indonesian version of the Zarit Burden Interview (ZBI) questionnaire and Cronbach alpha (α) was 0.931. Descriptive statistics were used to describe and categorize the family caregiver burden. Results: The results showed that the majority of participants had burden score in the category no burden – low burdens: 64 participants (40.0%), the mild-moderate burden category was 84 participants (52.5%), the moderate-severe burden was 11 participants (6.9%), very severe burden category was only 1 participant (0.6%). In addition, the demographic data showed that most of the participants were adult (55%), and the majority of caregivers are female (54.4%), the majority of education was senior high school (51.9%), for and most of the participants were unemployed (45.6%). Conclusion: This study was needed to provide evidence for evolving intervention among family caregivers.